Generalized Pre-Semi Closed and Pre-Semi Open Sets in Intuitionistic Fuzzy Topological Spaces - R. Revathy, P. Thirunavukarasu (Mathematical Statistician and Engineering Applications, 2022)
The features of generalised pre-semi closed sets (gps -closed) in a topological space are defined in this chapter, and they are appropriately situated between pre-closed sets and generalised pre- closed sets.